Serotonin - a complex, puzzling biomarker in Autism Spectrum Disorder - Ana Beatriz Branco Fevereiro (2020)
Background: Hyperserotonemia has been reported in Autism Spectrum Disorder (ASD) patients and their relatives. Due to serotonin's heuristic potential, this narrative review aims to discuss the biological plausibility of the serotonergic dysfunction hypothesis in ASD, as well as relevance and clinical implications of using serotonin as a biomarker. Methods: Human and animal studies addressing serotonergic dysfunction in ASD were surveyed, as well as articles reporting blood serotonin measurements in ASD patients and first-degree relatives. No time limit was applied, exclusively articles written in English were included. Results: Several lines of evidence confirm the involvement of the serotonergic system in ASD. Altered maternal and placental serotonin levels may influence the embryo, thus supporting the developmental hyperserotonemia model of autism. Hyperserotonemia is recorded in more than 25% of the ASD population and is thought to be a familiar trait, possibly related to platelet's handling of serotonin with several serotonergic genes conceivably implicated. Existing data highlights the reliability of hyperserotonemia as a biomarker and denotes serotonin as a potential nexus between the microbiome-gut-brain axis and ASD. Conclusions: The serotonin system plays a preponderant role in neurodevelopment, thus dysfunction of this neuromodulatory network might be implicated in ASD. Serotonin measurement would provide insights about pathophysiologic mechanisms and risk factors, identify homogenous subsets of patients with a delineated developmental trajectory, facilitate a more accurate diagnosis, while predicting treatment response, adverse reactions and help developing novel therapies. Further investigation is advised, as it will promote a faster translation of these basic science findings to clinical practice.